1996
DOI: 10.1097/00007890-199606270-00007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Determinants of Glucose Homeostasis After Pancreas Transplantation

Abstract: Although successful simultaneous pancreas and kidney transplantation (SPK) achieves normoglycemia in the majority of diabetic recipients with end-stage renal disease, little is known about the factors that influence long-term endocrine function. In this prospective study of 48 bladder-drained SPK patients, 209 oral glucose tolerance tests were performed between 3 months and 6 years after transplantation. Normal fasting glucose levels and systemic hyperinsulinemia were stable for up to 6 years after SPK. Multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
1
9
0
2
Order By: Relevance
“…An alternative interpretation is that the concurrence of decreased initial microvascular dysfunction and increased post-transplant C-peptide concentrations at day 2 post-transplant may indeed be due to relatively increased cleavage of C-peptide from pro-insulin, thereby indicating less pronounced islet injury. In this context, Nankivell and co-workers have identified short intraoperative surgical pancreas anastomosis time as a predictive parameter for increased post-transplant C-peptide levels, suggesting a noteworthy susceptibility of b-cells to ischemia/reperfusion injury (45). Therefore, systematic studies are required in order to fully elucidate the prognostic significance and relationship between early pancreatic microvascular dysfunction and post-transplant endocrine organ function in humans.…”
Section: Microvascular Impairment In the Early Reperfusion Period Aftmentioning
confidence: 99%
“…An alternative interpretation is that the concurrence of decreased initial microvascular dysfunction and increased post-transplant C-peptide concentrations at day 2 post-transplant may indeed be due to relatively increased cleavage of C-peptide from pro-insulin, thereby indicating less pronounced islet injury. In this context, Nankivell and co-workers have identified short intraoperative surgical pancreas anastomosis time as a predictive parameter for increased post-transplant C-peptide levels, suggesting a noteworthy susceptibility of b-cells to ischemia/reperfusion injury (45). Therefore, systematic studies are required in order to fully elucidate the prognostic significance and relationship between early pancreatic microvascular dysfunction and post-transplant endocrine organ function in humans.…”
Section: Microvascular Impairment In the Early Reperfusion Period Aftmentioning
confidence: 99%
“…The discrepancy between these results and the severe hyperinsulinemia with insulin resistance reported by other authors (6,7,15,21) can be explained by the low-dose steroid and cyclosporine treatment and by the absence of severe basal hyperinsulinemia in the SPK-S group. Moreover, several authors (22)(23)(24) remarked that insulin resistance after pancreas transplantation is not only related to systemic venous drainage but also depends on body weight, prednisone dose, and time after transplantation. However, minor changes could be observed between the groups: in the SPK-S group, glycemia was mildly decreased, whereas insulin and lipid oxidation values were increased when compared with the SPK-P group.…”
Section: Lipid Metabolism Studymentioning
confidence: 99%
“…Hyperinsulinemia complicates pancreas transplant with systemic drainage and most of these studies have average follow-up of one year or less (46,48,49,57,58). Nankivell et al (49) show an association of insulin resistance to corticosteroid therapy, body weight, and time posttransplant.…”
Section: Long-term Consequences Of Systemic Versus Portal Venous Draimentioning
confidence: 99%
“…Nankivell et al (49) show an association of insulin resistance to corticosteroid therapy, body weight, and time posttransplant. In contrast, Petruzzo et al (59) found little difference in insulin metabolism between portal and systemic drainage recipients with both groups falling in the normal range.…”
Section: Long-term Consequences Of Systemic Versus Portal Venous Draimentioning
confidence: 99%